فعالية برنامج تدريبي قائم على التعلم المستند إلى الدماغ لتنمية الوعي الفونولوجي وأثره على الذاكرة السمعية لدى التلاميذ ذوي العسر القرائي - عيسى، يسري أحمد سيد (دار سمات للدراسات والأبحاث, 2017)
هدفت الدراسة الحالية الى استقصاء فعالية برنامج تدريبي مقترح قائم على التعلم المستند إلى الدماغ لتنمية الوعي الفونولوجي ومعرفة أثره على الذاكرة السمعية لدى التلاميذ ذوي العسر القرائي. تكونت عينة الدراسة من (20) تلميذا من تلاميذ الصف الثاني الابتدائي الملتحقين ببرامج صعوبات التعلم بالمرحلة الابتدائية بمدرسة جعفر بن أبي طالب ومدرسة المثنى بن حارثة بمدينة الرياض خلال العام الدراسي 1436-1437 ه، تم تقسيمها إلى مجموعتين متجانستين إحداهما تجريبية والأخرى ضابطة تضم كل منها عشرة تلاميذ, ولتحقيق أهداف الدراسة تم تطبيق مقياس الوعي الفونولوجي (إعداد الباحث). مقياس الذاكرة السمعية (إعداد الباحث). اختبار المصفوفات المتتابعة لرافن للذكاء، البرنامج التدريبي المقترح القائم على التعلم المستند الى الدماغ (إعداد الباحث). وتوصلت النتائج إلي وجود فروق دالة إحصائيا عند مستوى 0.01 بين متوسطات رتب درجات المجموعة التجريبية ومتوسطات رتب درجات المجموعة الضابطة في القياس البعدي على مقياس الوعي الفونولوجي لصالح المجموعة التجريبية. كما وجدت فروق دالة إحصائيا عند مستوى 0.01 بين متوسطات رتب درجات المجموعة التجريبية في القياس القبلي ومتوسطات رتب درجاتهم في القياس البعدي علي مقياس الوعي الفونولوجي لصالح القياس البعدي. وكذلك توصلت أيضا إلى عدم وجود فروق دالة إحصائيا بين متوسطات رتب درجات المجموعة التجريبية في القياس البعدي ومتوسطات رتب درجاتهم في القياس التتبعي علي مقياس الوعي الفونولوجي مما يدل على استمرار فعالية البرنامج التدريبي. كما وجدت فروق دالة إحصائيا عند مستوى 0.01 بين متوسطات رتب درجات المجموعة التجريبية ومتوسطات رتب درجات المجموعة الضابطة في القياس البعدي علي مقياس الذاكرة السمعية لصالح المجموعة التجريبية. كما وجدت فروق دالة إحصائيا عند مستوى 0.01 بين متوسطات رتب درجات المجموعة التجريبية في القياس القبلي ومتوسطات رتب درجاتهم في القياس البعدي على مقياس الذاكرة السمعية لصالح القياس البعدي. وكذلك توصلت أيضا إلى عدم وجود فروق دالة إحصائيا بين متوسطات رتب درجات المجموعة التجريبية في القياس البعدي ومتوسطات رتب درجاتهم في القياس التتبعي علي مقياس الذاكرة السمعية.
The present study aimed at investigating The effectiveness of the training program is based on brain-based learning to the development of phonological awareness and its impact on the auditory memory of students with Dyslexic. The sample of the study consisted of (20) 2th primary grade enrolled in learning disabilities programs in primary stage at Jaafar bin Abi Talib School, Muthanna bin Haritha, in Riyadh in the academic year 1436-1437 AH. The students were divided into two groups: an experimental group and a control group and the other officer of each ten students, and to achieve the objectives of the study. Data collection was carried out by means of the phonological awareness Scale (prepared by the researcher), auditory memory scale (prepared by the researcher), aven's Progressive Matrices intelligence test , and the suggested Training Program is based on brain-based learning (prepared by the researcher). The results of the study revealed that there were significant statistical differences at (0.01) level of significance between the average ranks of the scores of the experimental and control groups in the post measurement on the phonological awareness Scale in favor of the experimental group. There were also significant statistical differences at (0.01) level of significance between the average ranks of the scores of the experimental group in the pre and post measurements of the phonological awareness Scale in favor of the post measurement. In addition, the results have shown that there was no significant statistical difference between the average ranks of the scores of the experimental group in the post and follow up measurements of the phonological awareness Scale which indicates the effectiveness of the program. Moreover, the results of the study revealed that there were significant statistical differences at (0.01) level of significance between the average ranks of the scores of the experimental and control groups in the post measurement on the auditory memory scale in favor of the experimental group. There were also significant statistical differences at (0.01) level of significance between the average ranks of the scores of the experimental group in the pre and post measurements of the auditory memory scale in favor of the post measurement. In addition, the results have shown that there was no significant statistical difference between the average ranks of the scores of the experimental group in the post and follow up measurements of the auditory memory Scale.
Keywords: التعلم المستند إلى الدماغ -- الوعي الفونولوجي -- الذاكرة السمعية -- العسر القرائي